2017
DOI: 10.1007/s11682-017-9727-6
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity neuroimaging biomarkers for the identification of amnestic mild cognitive impairment based on resting-state fMRI and a triple network model

Abstract: Many functional magnetic resonance imaging (fMRI) studies have indicated that Granger causality analysis (GCA) is a suitable method for revealing causal effects between brain regions. The purpose of the present study was to identify neuroimaging biomarkers with a high sensitivity to amnestic mild cognitive impairment (aMCI). The resting-state fMRI data of 30 patients with Alzheimer's disease (AD), 14 patients with aMCI, and 18 healthy controls (HC) were evaluated using GCA. This study focused on the "triple ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…Consequently, our results reveal that there might be a different impairment in FC of aSN in cognitive function across the aMCI and SCD. A recent study has indicated that within-SN CC between the dACC and the striatum is abnormal in aMCI when compared to the HC group (Yu et al, 2019), yet there are only a few studies on the altered CC patterns between the SN subnetworks (aSN and pSN networks) and the whole brain. Then, a previous study has proven that directed connectivity, implemented in GCA within DPABI, can reveal the compensatory or pathological mechanisms of AD to some extent (Menon, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, our results reveal that there might be a different impairment in FC of aSN in cognitive function across the aMCI and SCD. A recent study has indicated that within-SN CC between the dACC and the striatum is abnormal in aMCI when compared to the HC group (Yu et al, 2019), yet there are only a few studies on the altered CC patterns between the SN subnetworks (aSN and pSN networks) and the whole brain. Then, a previous study has proven that directed connectivity, implemented in GCA within DPABI, can reveal the compensatory or pathological mechanisms of AD to some extent (Menon, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the phases between normal aging and dementia, amnestic mild cognitive impairment (aMCI) subjects have a 10-15% possibility of developing into AD per year (Petersen et al, 2002;Yang et al, 2017). Subjective cognitive decline (SCD) is the stage referring to the elderly subjects that can last for decades earlier than the onset of dementia when persons subjectively complain of memory impairment without corresponding objective clinical manifestations, while person's scores are in the normal scope through standardized neuropsychological tests (Huang et al, 2018a;Funaki et al, 2019;Yu et al, 2019). Furthermore, converging evidence suggests that SCD poses risk for developing into MCI and AD, although it may likewise be of early preclinical stages of other neurodegeneration diseases (Berger-Sieczkowski et al, 2019;Caillaud et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the VAN, FPN, and DMN that are involved in a "triple network" hypothetic model (Menon, 2011) showed linear increases in their pairwise Vbetween-net. It has been proposed that such three networks are the "core" neurocognitive networks and their functional interactions are important for complex, high-order cognitive functions (Menon, 2011) and could be responsible for psychiatric and neurological disorders, such as depression (Berman et al, 2011), schizophrenia (Palaniyappan et al, 2011), and dementia (Zhou et al, 2010;Yu et al, 2017). Recently, researchers have found that the dynamic network switch supports flexible attention (mainly via DAN and VAN) and cognitive control (mainly via FPN) to meet time-varying changes in cognitive demands, and the loss of such optimized dynamics may lead to poor task performance in a decision-making task (Taghia et al, 2018).…”
Section: Increased Inter-network Fc Flexibilitymentioning
confidence: 99%
“…Three ICNs are particularly relevant for the cognitive and emotional information processing underlying social behavior: the central executive network (CEN), the salience network (SN), and the default mode network (DMN) (Menon, ). The CEN, also referred to as the frontoparietal network (Smith et al, ), consists primarily of nodes in the dorsolateral prefrontal cortex (dlPFC) and the lateral posterior parietal cortex (PPC) and has been associated with high‐level cognitive functions such as planning, goal‐directed decision making, and working memory (Menon, ; Seeley et al, ; White, Joseph, Francis, & Liddle, ; Yu et al, ). The SN, also referred to as the cingulo‐opercular network (Chen et al, ; Elton & Gao, ; Hahn et al, ) or the executive control network (Smith et al, ), is anchored in the dorsal anterior cingulate cortex (ACC) and the anterior insula and has been associated with the detection of and orientation to salient external stimuli as well as the autonomic integration of internal events (Menon, ; Seeley et al, ).…”
Section: Introductionmentioning
confidence: 99%